Lipase-Catalysed Synthesis of Fatty Aminoesters from Fatty Acids and Triethanolamine - Idris, Zainab (1998)
Fatty aminoesters containing mixtures of mono-, di- and triaminoesters were prepared from the enzyme-catalysed esterification of fatty acids and triethanolamine in organic solvents. Screening of enzymes suitable for the reactions was carried out by conducting the esterification reaction in n-hexane catalysed by 5 types of enzymes. Lipozyme 1M and Novozym 435 gave positive results indicated by the additional spots obtained on TLC analysis. FT1R analysis of the products indicated the presence ester linkage at wavenumber 1740 cm-1. Reduction in transmittance of the hydroxyl group at 3500 cm-1 indicated the disappearance of the hydroxyl group which was originally on the triethanolamine molecule. Effects of some reaction parameters such as time course, temperature, substrate mole ratio, substrate concentration, amount of enzyme and thermodynamic water activity were also investigated based on esterification of oleic acid and triethanolamine catalysed by Lipozyme 1M and Novozym 435 in n-hexane. Lipozyme 1M gave maximum conversion of 43.9% in 24 hours while Novozym 435 gave a maximum conversion of 37.34% in 6 hours. Optimum activity was obtained when the lipases catalyse the reaction at 50oC, at substrate concentration of 1.0 M in n-hexane. The lipases, however, behaved differently when preequilibrated in salt hydrates of different thermodynamic water activity. Novozym 435 exhibited high esterification activity when preequilibrated in the salt hydrates of lowest aw studied. On the other hand, Lipozyme 1M exhibited optimum esterification activity when preequilibrated in salts hydrates having aw value of 0.32. The activity of Lipozyme 1M was drastically reduced when the mole of triethanolamine was increased while Novozym 435 gave optimum activity when the substrates were reacted at 1:1 mole ratio. In addition, when the oleic.